Influence of Dy3+doping concentration on crystal structure and optical absorption of SnO2 nanoparticles. (2022) - Kumar, Pawan; Jakhar, Monu; Chauhan, Vaibhav; Pandey, Praveen C.
Abstract: The present work focuses on studying the effect of Dy doping on the structural and optical properties of SnO2 nanoparticles. We prepared the pure and Dy 3+ (1, 2, 3 and 4 at %) doped SnO2 nanoparticles sample using the co-precipitation method. Three different techniques XRD, UV– Vis & FTIR spectroscopy, have been used to characterize the prepared sample. X- Ray diffraction was used to determine the crystal structure and crystallite size of the prepared sample. Structural analysis by XRD confirms the substitution of Dy 3+ atoms on the sites of the host matrix (SnO2 ). Tetragonal rutile structure is formed by pure and Dy- doped at different concentrations. UV–VIS spectroscopy was used to study the optical properties of the sample. Optical study shows that the prepared sample is highly transparent and absorption increases with Dy doping concentration due to the increase of defect state. The band gap of the sample was found to decrease with increasing Dy concentration, this is due to defect level formation below the conduction band. FTIR spectroscopy determines the molecular geometry, inter and intermolecular interaction and type of functional group present in the prepared sample.